Interrelationships of Pressure-Dependent Hole Fraction and Elongational Viscosity in Polymer Melts - Fatma Sahin-Dinc; Ugur Yahsi; Tomas Sedlacek (Advances in Polymer Technology)
The elongational flow behavior of polyethylene, polypropylene, polystyrene, poly(methyl methacrylate), and polycarbonate, temperatures from 70 to 290 °C and pressures up to 70 MPa, is examined with the Yahsi-Dinc-Tav (YDT) model and its particular case known as the Cross model. The viscosity data employed in the range of 3-405 s-1 elongational rates were acquired from the literature at ambient and elevated pressures. The predictions and the fitting results of the proposed YDT model with the same measurement data are compared with the Cross model. The average absolute deviations of the viscosities predicted by the YDT model range from 0.54% to 9.44% at ambient and 1.95% to 6.28% at high pressures. Additionally, the linear formulations derived from the YDT model are employed to relate the viscosity with temperature and hole fraction (“thermooccupancy” function) at zero level of elongational rate and constant elongational rate along with constant elongational stress. The effects of the four viscosity parameters (such as transmission and activation energy coefficients in these equations) on the elongational viscosity are analyzed in detail and some conclusions on the structural differences for the polymers are discussed.